Fatal group ethylene glycol intoxication associated with hypothermia - Shcherbak, Oleksii; Kuzmina, Daria; Leontiev, Pavlo (The Ukrainian Scientific Medical Youth Journal, 2026)
in this case report, we present a fatal incident of group ethylene glycol poisoning involving three individuals. The bodies were discovered near a river in an advanced stage of decomposition and transported to the Department of Forensic Medical Examination at the State specialized institution "Kharkiv Regional Bureau of Forensic." In the absence of external signs of violent death, such cases are investigated using all available forensic methods, including autopsy, toxicological screening, and histological examination. The autopsy did not determine a definitive cause of death, and the histological examination revealed no features typically associated with ethylene glycol intoxication. However, qualitative forensic toxicological analysis confirmed the presence of ethylene glycol in renal and hepatic tissues. Clustered fatalities of this nature are relatively rare but do occur in forensic medical practice and require meticulous investigation to determine the underlying cause and circumstances of the death.